INTERPENETRASI ANTAR SUB-SISTEM DI DALAM SISTEM SOSIALMERESPON PERSOALAN BENCANA ASAP DI INDONESIA - F TRISAKTI HARYADI, ARIFUDIN, HERMIN INDAH WAHYUNI, (Jurnal Social Economic of Agriculture, 2018)
The haze disasters caused by peatland fires have caused reactions from each sub-system in the social system in Indonesia, which has led to an interpenetration within the social system. Interpenetration is a process that occurs within a social system where one event that occurs on one sub-system will impact to another sub-system, however it acts self-reference for reproduction within its own sub-system. Therefore, this research aims to analyze interpenetration among each sub-system within social system toward haze disaster in Indonesia. Qualitative research has been conducted in Riau and West Kalimantan provinces by analyzing discourse, both directly in the community and mass media. Discourses data in the community was collected through in-depth interviews, observations and Focus Group Discussion (FGD), while media discourse was taken from the discourse of the local media of Riau Pos and Pontianak Pos. From the analysis of the events of communication, it shows that interpenetration occurs in the entire social system. The economy, politics, law, science, education, religion, art, public health, and voluntary systems penetrate each other. Furthermore, interpenetration leads to new stability as a result of adjustments to ethical changes that exist within the social system.Keywords : haze disaster, interpenetration, peatland fires, social system